Efektifitas Penerapan Truth or Dare Untuk Meningkatkan maharah Kalam Siswa Kelas VIII di MTs Mamba'us Sholihin Senori - Nurul Sri Wulandari (Jurnal Pendidikan Bahasa Arab, 2023)
Speaking skills are one of the skills that must be achieved in teaching modern ?languages, including Arabic. Teaching speaking skills is not easy, but more difficult than the ?first language, because Arabic is a foreign language. So that there are several obstacles in ?learning Arabic speaking skills at SMP Mambaus Sholihin 8, most of them still experience ?difficulties in communicating using Arabic. Therefore, to increase students understanding of ?the lesson, especially speaking skills, and researcher is interested in applying it to speaking ?skills subjects. This research aims to improve students' speaking skills through the use of truth or dare game. In this study, researcher used a quantitative approach. The type ?used by researcher is experimental (Pre-Experimental Design), the first trial and the pre-?test and post-test groups. Researcher used the data in this study in the form of tests and ?documents?.?? The result of the research from the data analysis is “The Effectiveness Of ?Implementing The Game “Truth Or Dare” To Improve The Speaking Skills Of Class VIII ?Students Of SMP Mambaus Sholihin 8 Katerban Senori Tuban. Depending on the statistical ?data analysis with the symbol T test, the result is 18.84, so the interpretation of this value in ?the 1% table of the number of samples (degree of succession) 28 is 2.76, and at the 5% ?degree is 2.05. Because the calculated T value obtained is greater than the table T value both ?at 1% and 5% secnificase. The alternative hypothesis (Ha) is accepted and the null ?hypothesis (Ho) is rejected.?